2023
DOI: 10.3390/ijms241512295
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction in the Mitochondrial Membrane Potential in Aging: The Role of the Mitochondrial Permeability Transition Pore

Hagai Rottenberg

Abstract: It is widely reported that the mitochondrial membrane potential, ∆Ψm, is reduced in aging animals. It was recently suggested that the lower ∆Ψm in aged animals modulates mitochondrial bioenergetics and that this effect is a major cause of aging since artificially increased ∆Ψm in C. elegans increased lifespan. Here, I critically review studies that reported reduction in ∆Ψm in aged animals, including worms, and conclude that many of these observations are best interpreted as evidence that the fraction of depol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Our data showed that Mel treatment on SH-SY5Y neuronal cells attenuated the antioxidant activity causing oxidative stress conditions. This result was in accordance with the previous reports that showed increased oxidative stress in the hippocampal region of adult rats upon treatment with Mel [ 15 ]. Further in our study, we found that when DG-treated cells were exposed to Mel, more pronounced decrease in the antioxidant activity of the cells occurred, hence depicting huge oxidative stress in the cotreated group ( Figure 4(a) ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our data showed that Mel treatment on SH-SY5Y neuronal cells attenuated the antioxidant activity causing oxidative stress conditions. This result was in accordance with the previous reports that showed increased oxidative stress in the hippocampal region of adult rats upon treatment with Mel [ 15 ]. Further in our study, we found that when DG-treated cells were exposed to Mel, more pronounced decrease in the antioxidant activity of the cells occurred, hence depicting huge oxidative stress in the cotreated group ( Figure 4(a) ).…”
Section: Discussionsupporting
confidence: 94%
“…Aging is a complex biological process associated with a gradual decline in physiological functions, including those of the brain. The accumulation of oxidative stress and dysregulation of apoptosis are key contributors to the aging-related degeneration of neuronal cells [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased Ca 2+ and ROS both activate a large conductance channel in the mitochondrial inner membrane, the mitochondrial permeability transition pore (mPTP), whose opening disrupts the mitochondrial membrane potential (ΔΨ m ) [ 24 ]. We thus examined whether CSE treatment induces mPTP opening by assessing the attenuation of calcein fluorescence from mitochondrial regions labeled by TMRE (see methods).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal cytosolic Ca 2+ overload induces mitochondrial Ca 2+ influx via mitochondrial Ca 2+ uniporters, both of which can lead to enhanced mitochondrial ROS production [ 29 ]. This can activate a large conductance channel in the mitochondrial inner membrane (IMM) known as mitochondrial permeation transition pore (mPTP), and opening of mPTP decrease ΔΨm [ 24 ], that collapse protonmotive force and inhibits ATP synthesis. Prolonged opening of the mPTP allows cytoplasmic solutes to flow into the mitochondria, causing massive swelling of the IMM, rupture of the outer membrane, that cause cytochrome c release and cell death [ 30 ].…”
Section: Discussionmentioning
confidence: 99%